DETERMINATION OF MAGNESIUM AND IRON IN GOAT’S MILK POWDER BY FLAME ATOMIC ABSORPTION SPECTROPHOTOMETRY - Kusumaningtyas, H.; Febiana, H.; Septiani, L. (Indonesian Journal of Chemistry and Environment, 2019)
This research aims to determine the levels of magnesium and iron in goat milk powder. The method of this research was atomic absorption spectrophotometry. The research subject was goat milk powder. Moreover, the research object was the amount of magnesium and iron in goat?s milk powder. Before analyzing, the first step was removing organic substances in the sample that could interfere the analysis by dissolved it in concentrated nitric acid and heated. Based on the measurement using flame atomic absorption spectrophotometry method, absorbance and concentration of magnesium and iron in the sample were obtained. The analysis showed that the levels of magnesium and iron in the sample were 0.0032 mg/g and 0.0218 mg/g.